2017
DOI: 10.1016/j.tmaid.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

High altitude illness in pilgrims after rapid ascent to 4380 M

Abstract: HAH and AMS were common in pilgrims ascending rapidly to 4380 m. There were 11 cases of HACE, treated with dexamethasone, supplemental oxygen and descent. There were no fatalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…High-altitude environments, accompanied by the typical characteristics of hypobaric hypoxia, strong ultraviolet radiation, low temperature and high humidity, can easily induce pathological damage to various tissues, and in severe cases, can develop into brain or pulmonary edema. Clinical symptoms include headache, light-headedness, insomnia, fatigue and other neurological symptoms, as well as cough, progressive dyspnea and other signs of lung injury (Archer et al, 2020;Wang et al, 2018;Wu et al, 2018;Zafren et al, 2017). Pathological results show that meldonium can significantly improve cerebral blood flow reduction, alveolar dilatation, alveolar interstitial rupture and thickening induced by acute hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…High-altitude environments, accompanied by the typical characteristics of hypobaric hypoxia, strong ultraviolet radiation, low temperature and high humidity, can easily induce pathological damage to various tissues, and in severe cases, can develop into brain or pulmonary edema. Clinical symptoms include headache, light-headedness, insomnia, fatigue and other neurological symptoms, as well as cough, progressive dyspnea and other signs of lung injury (Archer et al, 2020;Wang et al, 2018;Wu et al, 2018;Zafren et al, 2017). Pathological results show that meldonium can significantly improve cerebral blood flow reduction, alveolar dilatation, alveolar interstitial rupture and thickening induced by acute hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Among pilgrims visiting Gosainkunda, a sacred lake at 4380 m, for Janai Purnima festival, the incidence of AMS was found to be 34% [ 7 ]. Another study reported AMS in around 29% patients, including those with HACE [ 8 ]. Study in the Annapurna trekking region showed prevalence of AMS between 34% and 57% [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the religious zeal, the high cost of lodging and buying meals during pilgrimage may also contribute to rapid ascent. The majority of pilgrims at Gosainkund Lake only stay for one night 4. This sentiment of finishing the pilgrimage as early as possible also contributes to the rapid rate of ascent among the pilgrims.…”
Section: Global Health Problem Analysismentioning
confidence: 99%